Freedom of Panorama Terkait Pelindungan Karya Cipta di Ruang Publik Berdasarkan Hukum Hak Cipta dan Hukum Teknologi Informasi dan Komunikasi - Danetta Leoni Andrea; Rika Ratna Permata; Tasya Safiranita (Kyadiren, 2020)
The presence of digital technology makes it easier for humans to create unlimited creative contents, for example in perpetuating copyrighted works in the public space and then being able to use them commercially or non-commercially on platforms or online media. This raises a problem, what if copyrighted works in public spaces that are immortalized and uploaded to online media are categorized as copyright infringement. Where in some countries, taking a portrait of a copyrighted work in a public space can only be done under the provisions of the Freedom of Panorama. The copyright law (UUHC) has not regulated the Freedom of Panorama and the protection of copyrighted works in the public space, as well as efforts to prevent violations by the government and platform providers have also not maximally provided protection for copyrighted works for uploaded contents